Revolutionizing English Vocabulary Learning: Harnessing the Power of TikTok Videos - jabri, Umiyati; Nurwahida, Nurwahida; Ismail, Ismail; Hasan, Hasan (Edumaspul: Jurnal Pendidikan, 2024)
The study on Revolutionizing English Vocabulary Learning: Harnessing the Power of TikTok Videos aims to determine whether the TikTok app can help seventh grade students at SMPN 4 Enrekang enhance their English vocabulary. The research methodology employed is experimental research, with the design being a quasi-experimental design, specifically the Pretest-Posttest Control Group design. It involves two variables: the independent variable (vocabulary) and the dependent variable (TikTok). Based on the average scores, the pretest results for the control class were 21.33, and for the experimental class, 21.86. The posttest scores showed an increase, with the control class averaging 53.87 and the experimental class 61.87. From these results, it is evident that there is a difference in the average learning outcomes between the control and experimental classes of 8.00, indicating that learning outcomes through the use of TikTok videos are higher than those achieved using the lecture method. The results of the study, conducted with seventh grade students at SMP Negeri 4 Enrekang, conclude that TikTok videos are effective in increasing students' English vocabulary. This conclusion is based on the results of the independent sample t-test calculation, where the calculated t-value is greater than the t-table value (2.362 > 2.010) and the significance value is less than 0.05 (p = 0.022 < 0.05). Therefore, it can be concluded that there are significant differences in the English vocabulary acquisition outcomes between students in the experimental and control classes of the seventh grade.